UNIT 14.22 Using CellX to Quantify Intracellular Events. Issue 1 (January 2013) - Mayer, Christian; Dimopoulos, Sotiris; Rudolf, Fabian; Stelling, Jörg
Abstract: Methods to quantify features of individual cells using light microscopy have become widely used in biology. A multitude of computational tools has been developed for image analysis; however, they are often only for specific cell types and microscopy techniques. This unit describes CellX, an open‐source software package for cell segmentation, intensity quantification, and cell tracking on a variety of microscopy images. CellX can perform cell segmentation largely independently of cell shapes, and can also cope with images that are crowded with cells. The basic protocol describes how to use CellX for cell segmentation and quantification. This protocol remains the same whether there is a collection of images to be analyzed or whether cell tracking on a sequence of images is to be performed. The CellX output comprises control images for visual validation, text files for post‐processing statistics, and MATLAB objects for advanced subsequent analysis. Curr. Protoc. Mol. Biol. 101:14.22.1–14.22.20. © 2013 by John Wiley & Sons, Inc.